Modernisasi Dayah Darul Huda Kota Langsa, 1962-2005 - Idrus Idrus; Budi Agustono; Nuhung Nuhung (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2020)
This article discusses the history of Acehnese traditional Islamic educational institutions called dayah. The discussion focused on the modernization of Dayah Darul Huda in Langsa City. The historical method is used to trace historical facts and reconstructed in the form of historiography. The results of the study found that the factors that encourage the development of dayah to a more modern system include: curriculum modernization; management; as well as infrastructure. The value contained in the vision and mission of modern Dayah Darul Huda education is the desire to make changes, improvements and development in matters especially science. Another factor that cannot be ignored is that some people still choose general education institutions as the main education for their children.